Food retailing and sustainable development : European perspectives - Lavorata, Laure; Sparks, Leigh (Emerald Publishing Limited, 2018)
Faced with dwindling resources and the challenge of climate change, companies are seeking to enhance production while consuming fewer resources. At the same time, consumers are altering their behaviors by seeking local production or bulk buying products. Retailers, as boundary spanners between consumers and producers, have a major role in initiating change and sustainable development. Part one of this book analyzes the sustainable development practices of retailers within and between different European countries and presents case studies that consider best practices on this topic. Retailer include: Carrefour, Casino, Auchan, Leclerc, Intermarché and System U in France; Inditex, Cortefiel and MANGO in Spain; Edeka, Rewe, Schwarz-Group (with Lidl and Kaufland) and Aldi in Germany; and Tesco and Marks & Spencer in UK. International retailers in Poland are considered to better understand cross country activities. Part two underlines the challenges faced by European retailers in the wake of societal and technological changes. The consumers' role and their sustainable development practices are analyzed to understand the impact on retailing and the main risks for retailers. This book will appeal to academics, students and professional educators alike, providing a crucial understanding of retailers' practices in different countries and their impact on consumers.
Keywords: Food industry and trade -- Europe.; Food supply -- Moral and ethical aspects -- Europe.; Aliments -- Approvisionnement -- Aspect moral -- Europe.; Sustainability.; BUSINESS & ECONOMICS -- Industries -- General.; Food industry and trade; Food supply -- Moral and ethical aspects; Europe